2017
DOI: 10.1007/978-3-319-60733-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Diseases as Model of Neurodegeneration

Abstract: "Mitochondria" partially autonomous sophisticated cellular organelle involved in a wide range of crucial cellular functions, well known as the power house of the cell where ATP (adenosine triphosphate) production takes place, that is the cellular source of energy.Mitochondria has its own genome, however proper functioning of the mitochondria is dependent upon the coordinated expression of both nuclear and mitochondrial encoded gene products. Peculiar maternal inheritance of mitochondrial DNA has led the scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Mounting evidence suggests that mitochondrial dysfunction is closely related to the pathogenesis of several neurodegenerative disorders, including AD (Müller et al, 2010 ; Calkins et al, 2011 ; Selim and Hassaan, 2017 ; Weng et al, 2017 ). Mitochondrial dysfunction is mainly manifested as an energy metabolism disorder, ETC damage, mitochondrial dynamics disorder and related descriptors (Minoshima et al, 1997 ; Etminan et al, 2005 ; Chan, 2006b ; Aung et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that mitochondrial dysfunction is closely related to the pathogenesis of several neurodegenerative disorders, including AD (Müller et al, 2010 ; Calkins et al, 2011 ; Selim and Hassaan, 2017 ; Weng et al, 2017 ). Mitochondrial dysfunction is mainly manifested as an energy metabolism disorder, ETC damage, mitochondrial dynamics disorder and related descriptors (Minoshima et al, 1997 ; Etminan et al, 2005 ; Chan, 2006b ; Aung et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in mitochondrial DNA replication result in mtDNA mutation, multiple deletions, and mtDNA molecule depletion [46]. Moreover, mtDNA has a higher mutation rate than nuclear DNA because it lacks histone protection and a DNA damage repair system and approaches the electron transport chain (ETC) system, which produces oxygen-free radicals [47]. Existing studies have shown that mtDNA mutations contribute to many diseases, such as PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique structural properties of mitochondrial genes, the frequency of DNA mutations is much higher than that of nuclear DNA (Selim and Hassaan, 2017). Recent studies have shown a positive correlation between mitochondrial dysfunction and PCOS, and PCOS-IR mitochondrial genome mutations have become a research hotspot (Table 1).…”
Section: Metabolic Reproductive Diseases and Mitochondrial Dysfunctionmentioning
confidence: 99%